Evaluation of an oil dispersion formulation of imidacloprid as a drench against Rhynchophorus ferrugineus (Coleoptera, Curculionidae) in young palm trees - Llácer, Elena; Negre, Maria; Jaques, Josep A. (2017)
BACKGROUND: The red palm weevil, Rhynchophorus ferrugineus (Olivier), is a phytophagous insect that feeds on soft succulent tissues of most palm species and is considered the main palm pest in the Middle East and the Mediterranean Basin. The aim of this study was to test the efficacy of imidacloprid oil dispersion (OD) as a drench in preventive and curative treatments against R. ferrugineus in Phoenix canariensis, Washingtonia robusta, Washingtonia filifera and Trachycarpus fortunei. RESULTS: Levels of infestation were highest in P. canariensis. There was no infestation in W. filifera. Mean efficacies of 100 and 94% were obtained in preventive and curative treatments respectively. High efficacies in preventive treatments (mean 95.4%) lasted for up to 45 days after application. CONCLUSION: The high efficacies and persistence of imidacloprid OD applied as a drench in young palms show the potential of this product for the management of R. ferrugineus. Copyright (C) 2011 Society of Chemical Industry